Relacje interpersonalne z perspektywy psychologii rozwoju człowieka = Interpersonal relations from the point of view of developmental psychology - Herberger, Jerzy; Kozłowska, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a review based on the analyses of chosen theories of psychological development (mainly postpsychoanalytic and life span psychology). Its primary purpose is to introduce a deeper understanding of how the course of life can influence the functioning of an individual in interpersonal connections. It is mainly addressed to sociologists and educators (teachers).
Keywords: relacje; związki międzyludzkie; rozwój; relations; interpersonal connections; development